Oral manifestations of HIV infection in children and adults receiving highly active anti-retroviral therapy [HAART] in Dar es Salaam, Tanzania - Mikx Frans HM; Mugusi Ferdinand; Moshi Mainen J; Kikwilu Emil; Simon Elison NM; Matee Mecky IN; Hamza Omar JM; Verweij Paul E; van der Ven André JAM (BMC, 2006)
Abstract Background The aim of the study was to compare the prevalence and types of HIV-related oral lesions between children and adult Tanzanian patients on HAART with those not on HAART and to relate the occurrence of the lesions with anti-HIV drug regimen, clinical stage of HIV disease and CD4+ cell count. Methods Participants were 532 HIV infected patients, 51 children and 481 adults, 165 males and 367 females. Children were aged 2-17 years and adults 18 and 67 years. Participants were recruited consecutively at the Muhimbili National Hospital (MNH) HIV clinic from October 2004 to September 2005. Investigations included; interviews, physical examinations, HIV testing and enumeration of CD4+ T cells. Results A total of 237 HIV-associated oral lesions were observed in 210 (39.5%) patients. Oral candidiasis was the commonest (23.5%), followed by mucosal hyperpigmentation (4.7%). There was a significant difference in the occurrence of oral candidiasis (χ2 = 4.31; df = 1; p = 0.03) and parotid enlargement (χ2 = 36.5; df = 1; p = 0.04) between children and adults. Adult patients who were on HAART had a significantly lower risk of; oral lesions (OR = 0.32; 95% CI = 0.22 - 0.47; p = 0.005), oral candidiasis (OR = 0.28; 95% CI = 0.18 - 0.44; p = 0.003) and oral hairy leukoplakia (OR = 0.18; 95% CI = 0.04 - 0.85; p = 0.03). There was no significant reduction in occurrence of oral lesions in children on HAART (OR = 0.35; 95% CI = 0.11-1.14; p = 0.15). There was also a significant association between the presence of oral lesions and CD4+ cell count < 200 cell/mm3 (χ2 = 52.4; df = 2; p = 0.006) and with WHO clinical stage (χ2 = 121; df = 3; p = 0.008). Oral lesions were also associated with tobacco smoking (χ2 = 8.17; df = 2; p = 0.04). Conclusion Adult patients receiving HAART had a significantly lower prevalence of oral lesions, particularly oral candidiasis and oral hairy leukoplakia. There was no significant change in occurrence of oral lesions in children receiving HAART. The occurrence of oral lesions, in both HAART and non-HAART patients, correlated with WHO clinical staging and CD4+ less than 200 cells/mm3.